Diagnostics and treatment of psoriasis vulgaris: guidelines of the Polish Dermatological Society. Part I: mild psoriasis, psoriasis in children - Szepietowski, Jacek; Adamski, Zygmunt; Chodorowska, Grażyna; Gliński, Wiesław; Kaszuba, Andrzej; Placek, Waldemar; Rudnicka, Lidia; Reich, Adam (Dermatology Review/Przegląd Dermatologiczny, 2012)
Psoriasis is a chronic inflammatory skin disease affecting about 1-3% of the Caucasian population. Psoriasis is still not a curable disease, however, during the last couple of years rapid progress in the development of new anti-psoriatic therapies has been observed. Taking into account the increasing number of available treatment modalities, we tried to systematize current therapeutic strategies in Poland. These recommendations were established to help Polish dermatologists care for patients with this disease. In this part of the recommendations we describe basic principles of patient classification, topical therapy, management of patients with nail psoriasis and treatment of psoriasis in children. We hope that our suggestions will be valuable for physicians in their daily clinical practice. However, we would like to underline that the final decision about therapy should always be made individually for every patient, based on the patient’s current clinical status and also taking into consideration the most up-to-date scientific literature data.